Casein and Ag nanoparticles: Synthesis, characterization, and their application in biopolymer‐based bilayer film. Issue 9 (18th June 2019) - Bora, Anupama; Mishra, Poonam
Abstract: In the present investigation, casein nanoparticles and silver nanoparticles (AgNPs) were synthesized separately and the synthesized nanoparticles were incorporated into the bilayer film. Casein nanoparticles were produced using desolvation techniques, whereas AgNPs were synthesized using casein protein. The synthesized nanoparticles were characterized by scanning electron microscope (SEM), field emission electron microscope (FESEM), and UV–Visible spectra. UV spectra and SEM revealed that the pH had a significant effect on the size of both casein nanoparticles and AgNPs. AgNPs, synthesized at pH 13, were spherical in shape with average particle size of 10–25 nm and were stable up to 80 days. All the synthesized AgNPs showed 7–14 mm of zone of inhibition against growth of Escherichia coli . Incorporation of AgNPs and casein nanoparticles into sodium alginate/casein bilayer film improved the oxidative stability of packed almond oil during storage. Peroxide value of oil was increased from 8.02 meq/kg to 11.5 meq/kg only when stored in nanoparticles containing biopolymer film. Practical applications: Edible film is a better alternative of plastic materials, but poor shelf life and mechanical properties of the film restrict the application of edible films in food Industries. Incorporation of antibacterial agent can improve the shelf life of biodegradable film. So, in present investigation, casein nanoparticles and AgNPs were synthesized separately. Casein nanoparticles were produced using desolvation techniques, whereas AgNPs were synthesized through mediation of casein protein. Synthesized nanoparticles were characterized by SEM, FESEM, and UV–Visible spectra. The synthesized nanoparticles were incorporated into pectin–sodium alginate/casein bilayer film. Incorporation of AgNPs and casein nanoparticles in bilayer improved the oxidative stability of almond oil during storage.